Addressing Challenges in the Application of Animal Movement Ecology to Aquatic Conservation and Management - Ogburn, Matthew B.; Harrison, Autumn-Lynn; Whoriskey, Frederick G.; Cooke, Steven J.; Mills Flemming, Joanna E.; Torres, Leigh G. (Frontiers in Marine Science, 2017)
The dynamic nature of most environments forces many animals to move to meet their fundamental needs. This is especially true in aquatic environments where shifts in spatial ecology (which are a result of movements) are among the first adaptive responses of animals to changes in ecosystems. Changes in the movement and distribution of individuals will in turn alter population dynamics and ecosystem structure. Thus, understanding the drivers and impacts of variation in animal movements over time is critical to conservation and spatial planning. Here we identify key challenges that impede aquatic animal movement science from informing management and conservation, and propose strategies for overcoming them. Challenges include: 1) Insufficient communication between terrestrial and aquatic movement scientists that could be increased through cross-pollination of analytical tools and development of new tools and outputs; 2) Incomplete coverage in many studies of animal space use (e.g. entire life span not considered); 3) Insufficient data archiving and availability; 4) Barriers to incorporating movement data into decision-making processes; and 5) Limited understanding of the value of movement data for management and conservation. We argue that the field of movement ecology is at present an under-tapped resource for aquatic decision-makers, but is poised to play a critical role in future management approaches and policy development.